ANALISIS PENERAPAN MODEL PEMBELAJARAN PROBLEM-BASED LEARNING (PBL) PADA PELAJARAN IPAS SD - Fadillah, Krisna Farhan; Siska Mega Diana; Niken Yuni Astiti; Sowiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem addressed in this study is the need to understand and describe the implementation of the Problem-Based Learning (PBL) model, particularly in Science and Social Studies (IPAS) subjects at the elementary school level. This study aims to analyze the implementation of the PBL model in IPAS learning at SD Tri Sukses Natar, South Lampung, focusing on how each stage of the PBL syntax is carried out by the teacher. This research employed a descriptive qualitative approach using a case study method. In this study, the teacher was positioned as the primary subject, while the principal and students served as supporting informants. Data were collected through observation, interviews, and document analysis. The findings indicate that the teacher has implemented the PBL syntax in IPAS learning, as reflected in the activities of problem orientation, organizing students, guiding the investigation process, presenting students’ work, and conducting learning reflection.